PENDEKATAN STEAM BERBASIS VIDEO PEMBELAJARAN PADA MATERI BANGUN DATAR SISI BANYAK - Sumini; Bektiningsih; Arum Susilowati; Yulia Maftuhah H; Anatri Desstya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the planning of learning materials for many-sided flat buildings with a STEAM approach based on learning videos. The research in this article is a qualitative descriptive approach that describes logically and systematically the planning oflearning materials for many-sided flat buildings with learning videos. The research subjects involved the sixth-grade teachers and principals in elementary school. The data collected was a descriptive narration about the planning of learning material for many-sided flat buildings and learning documents. Data collection techniques were carried out through interviews and documentation. In addition, the data were analyzed with the stages of data reduction, data displays, drawing conclusions, and verification. The validity of the data was validated by using triangulation of sources and methods. Triangulation of sources was validated by checking the interview results of lesson plans with teachers and principals. The triangulation method was carried out by comparing the interview results and the results of document observations. The documents on the examined learning plan were the lesson plans or RPP, teaching materials, LKPD, learning media, and assessments. The results showed that the STEAM learning applied by the sixth-grade elementary school teachers had fulfilled the elements of science, technology, engineering, and math. Still, the element of art had not been fulfilled